Meteorological and snow accumulation gradients across Dome C, East Antarctic plateau. (19th May 2015) - Genthon, C.; Six, D.; Scarchilli, C.; Ciardini, V.; Frezzotti, M.
ABSTRACT: In situ observations show that snow accumulation is ∼10% larger 25 km north than south of the summit of Dome C on the east antarctic plateau. The mean wind direction is southerly. Although a slight slope‐related diverging katabatic flow component is detectable, the area is an essentially flat (∼10 m elevation change or less) homogeneous snow surface. The European Center for Medium‐range Weather Forecasts meteorological analyses data reproduce a significant accumulation gradient and suggest that 90% of the the mean accumulation results from the 25% largest precipitation events. During these events, air masses originate from coastal areas in the north rather than from inland in the south. Radiative cooling condensation occurs on the way across the dome and as the moisture reservoir is depleted less snow is dumped 25 km south than north, with little direct impact from the local (50‐km scale) topography. Air masses are warmer on average, and warmer north than south, when originating from the coast. This marginally affects the mean temperature gradients. The moisture gradients are more affected because moisture is nonlinearly related to temperature: the mean atmospheric moisture is larger north than south. Significant meteorological and hydrological gradients over such relatively small distances (50 km) over locally flat region may be an issue when interpreting ice cores: although cores are drilled at the top of domes and ridges where the slopes and elevation gradients are minimal, they sample small surfaces in areas affected by significant meteorological and hydrological spatial gradients.